Step
*
1
of Lemma
bag-union-is-single
1. T : Type
2. x : T
3. bbs : bag(bag(T))
4. bag-union(bbs) = {x} ∈ bag(T)
⊢ ↓∃bbs':bag(bag(T)). ((bbs = {x}.bbs' ∈ bag(bag(T))) ∧ (bag-union(bbs') = {} ∈ bag(T)))
BY
{ (BagInd (-2) THEN Auto) }
1
1. T : Type
2. x : T
3. bag-union([]) = {x} ∈ bag(T)
⊢ ↓∃bbs':bag(bag(T)). (([] = {x}.bbs' ∈ bag(bag(T))) ∧ (bag-union(bbs') = {} ∈ bag(T)))
2
1. T : Type
2. x : T
3. u : bag(T)
4. v : bag(T) List
5. (bag-union(v) = {x} ∈ bag(T))
⇒ (↓∃bbs':bag(bag(T)). ((v = {x}.bbs' ∈ bag(bag(T))) ∧ (bag-union(bbs') = {} ∈ bag(T))))
6. bag-union([u / v]) = {x} ∈ bag(T)
⊢ ↓∃bbs':bag(bag(T)). (([u / v] = {x}.bbs' ∈ bag(bag(T))) ∧ (bag-union(bbs') = {} ∈ bag(T)))
Latex:
Latex:
1.  T  :  Type
2.  x  :  T
3.  bbs  :  bag(bag(T))
4.  bag-union(bbs)  =  \{x\}
\mvdash{}  \mdownarrow{}\mexists{}bbs':bag(bag(T)).  ((bbs  =  \{x\}.bbs')  \mwedge{}  (bag-union(bbs')  =  \{\}))
By
Latex:
(BagInd  (-2)  THEN  Auto)
Home
Index